The Effect of The Jigsaw Teaching Technique on The Students' Reading Comprehension at Seventh Grade of UPTD SMPN 5 Pematangsiantar - Bonita Anjelina Sihombing; Bloner Sinurat; Dumaris Elseria Silalahi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to determine the effect of jigsaw teaching techniques on reading comprehension of Grade VII students at UPTD SMPN 5 Pematangsiantar in 2024/2025 school year. This research uses a quantitative research design by applying a quasi-experimental design. In this design, the research subjects were divided into two groups: VII-1 as experimental group and VII-2 as control group. The treatment was given only to the experimental group. The experimental group was treated with the jigsaw technique while the control group was treated without the jigsaw technique. The subjects of this research were seventh grade students (VII-1 and VII-2) of UPTD SMPN 5 Pematangsiantar with 62 students. The researcher used multiple choice questions as an instrument to assess students' reading comprehension. The results of data analysis showed that the mean score of the experimental class increased from 67.81 up to 81.25 while the mean score of the control class increased from 69.21 up to 73.43. A t-test was performed at the 5% significance level. The calculated t-value of 4.25 exceeds the t-table value of 1.670 (t-test > t-table). This indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Therefore, it can be concluded that the use of jigsaw teaching technique has a significant effect on the reading comprehension of seventh grade students at UPTD SMPN 5 Pematangsiantar.